PRESCHOOL: YESTERDAY, TODAY, TOMORROW - Аlieva Khosiyatkhon Khusniddinovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the establishment of an effective pre-school education system aimed at ensuring the formation of the next generation, the preparation of educational-methodical, didactic materials, and artistic literature reflecting national, cultural, and historical values, and the arousal of interest in reading books from childhood, as well as the implementation of the project under a public-private partnership agreement.